The Actors Studio's Uda dan Dara: An Adaptation-Reinvention - D. Muralitharan Pillai, (Wacana Seni Journal of Arts Discourse, 2016)
As the dynamic duo of Malaysian theatre, Dato' Faridah Merican and Joe Hasham, founders of The Actors Studio, are among the first generation of pioneering theatre practitioners that have toiled to shape the landscape of performing arts in Malaysia. Their insights offer opportunities to the new generation of theatre enthusiasts for the interrogation of theatrical and cultural sources in theatre practice. In 2015, The Actors Studio Seni Teater Rakyat premiered Dato' Dr. Usman Awang's Uda dan Dara to the Malaysian audience. This review attempts to unearth and validate the justification behind Dato' Faridah Merican and Joe Hasham's adaptation-reinvention treatment of Dato' Dr. Usman Awang's Uda dan Dara play.